Consumo de bebida alcoólica entre adolescentes: prevalência e fatores associados - Souza, Jorge Andrade (2018)
This study aims to estimate the prevalence and factors associated with alcohol consumption among adolescents enrolled in a public school in the city of Salvador, Bahia. This is an exploratory cross-sectional epidemiological study with 245 elementary and middle school students aged between 10 and 19 years. For the selection of participants, stratified random sampling was performed, admitting an error of 0.05 with a statistical significance level of 5%. The data collection instrument was a self-administered questionnaire and data analysis was done through logistic regression using the stepwise procedure in SPSS 17.0 software. Alcohol consumption among students was 60.8% and the initial age of alcohol intake by adolescents ranged from 06 to 18 years, with a mean of 12.9 years. Regarding race / color, 41.2% of schoolchildren declared themselves pardos and 54.3% belonged to females. The practice of paid activity was reported by 18.8% of young people, while 55.9% claimed to have some kind of religion. Almost all students reported living with their parents (93.9%), non-smokers (95.9%), not having a bad school performance (93.5%) and being single (96.7%). The multivariate logistic regression analysis revealed a statistically significant association (p <0.05) of three of the eleven covariates related to the endpoint studied (alcohol consumption at least once in life), be they, age (p = 0.00), consumption of alcoholic beverages by friends (p = 0.013) and having family members who drink too much (0.026). The study made it possible to identify the high prevalence of alcohol consumption and / or experimentation among schoolchildren and the importance of family and friends influence in initiating this consumption by adolescents. It is necessary to create strategies aimed at behavioral changes related to alcohol consumption, since it is a vulnerable group that is experiencing a phase of intense exposure to risk behaviors.